High-throughput analysis reveals disturbances throughout the cell caused by Arabidopsis UCP1 and UCP3 double knockdown - Lima, Rômulo Pedro Macêdo [UNESP]; Oliveira, Jakeline Santos [UNESP]; do Nascimento, Leandro Costa; Labate, Mônica Teresa Veneziano; Labate, Carlos Alberto; Barreto, Pedro [UNESP]; Maia, Ivan de Godoy [UNESP] (Elsevier, 2024)
Three genes encoding mitochondrial uncoupling proteins (UCPs) have been described in Arabidopsis thaliana (UCP1 to UCP3). In plants, UCPs may act as an uncoupler or as an aspartate/glutamate exchanger. For instance, much of the data regarding UCP functionality were obtained for the UCP1 and UCP2 isoforms compared with UCP3. Here, to get a better understanding about the concerted action of UCP1 and UCP3 in planta, we investigated the transcriptome and metabolome profiles of ucp1 ucp3 double mutant plants during the vegetative phase. For that, 21-day-old mutant plants, which displayed the most evident phenotypic alterations compared to wild type (WT) plants, were employed. The double knockdown of UCP1 and UCP3, isoforms unequivocally present inside the mitochondria, promoted important transcriptional reprogramming with alterations in the expression of genes related to mitochondrial and chloroplast function as well as those responsive to abiotic stress, suggesting disturbances throughout the cell. The observed transcriptional changes were well integrated with the metabolomic data of ucp1 ucp3 plants. Alterations in metabolites related to primary and secondary metabolism, particularly enriched in the Alanine, Aspartate and Glutamate metabolism, were detected. These findings extend our knowledge of the underlying roles played by UCP3 in concert with UCP1 at the whole plant level.
Keywords: Abiotic stress; Chloroplast; Double mutant; Metabolome; Mitochondria; Uncoupling protein